Foreign Market Entry Strategies in Retail Banking: Choosing an Entry Mode in a Landscape of Constraints - Petrou, Andreas (My University, 2009)
International expansion by retail banks can involve different modes of foreign entry, the most common being acquisitions, start-ups and joint ventures. But there is only limited consensus over which represents the best option, and banks choose the same or different modes when entering different countries. This article investigates the question of how managers make these choices by testing a mode selection model based on the perceptions of managers involved in 124 foreign market entries. The model considers their control and resource objectives, their willingness to trade off control for access local resources and the constraints on their entry: levels of local regulation, home/host country differences and entrants' resources. The results show that internationalizing banks choices of entry mode are influenced by managers' desire for control over their foreign ventures and by their local market resource requirements, as well as by foreign regulatory constraints and the differences between home and foreign markets - but not by entrant's size. Identifying the factors influencing banks' entry mode choices allows us to point out a number of key factors managers should take into account when planning their internationalization strategies.
Keywords: Different modes; Access control; Laws and legislation; Managers; Commerce; Βanking